SAMPAH PLASTIK DALAM KARYA SENI LUKIS REALIS KONTEMPORER - Salman Hijrah; Erfahmi Erfahmi (Universitas Negeri Padang, 2020)
The creation of this final work aims to visualize the problem of plastic waste as an idea in the creation of contemporary painting. This work presents human figure formed from plastic rubbish. The embodiment method of this final work goes through five stages: preparation, elaboration, synthesis, concept realization, and completion. This work reveals that the amount of plastic waste can have negative effects on nature, animals, dan humans. The author succeeded in realizing 10 works with the title: bacot, the predator, more human than human, coboy, transplant, durable, imagery, consumptive, place of delivery, benamg hope.Keywords: Plastic Waste, Painting, Contemporary Realist